Maternal Factors Associated with Low Birth Weight Among Neonates Born at Thika Level 5 Hospital in Kiambu County, Kenya - Kenyanya, Joyce Osebe; Kikuvi, Gideon; Wanzala, Peter; Nyagero, Josephat (International Journal of Health Sciences, 2023)
Purpose: To determine maternal factors associated with low birth weight among neonates born at Thika Level Five Hospital in Kiambu County, Kenya. Methodology: Cross sectional convergent design was employed. The target group composed of mothers who delivered in the hospital during the study period (July-August, 2019). Census method was used to recruit participants for a quantitative study. Purposive sampling was used to select participants for FGDs and KIIs. Sample size was determined using the Cochran formula. Desired sample size was 210 mothers which was adjusted to 215 participants. Independent variables included: socio-demographic, socio-economic, socio-cultural, behavioral, and health of the mothers. Dependent variable was LBW which was classified further into LBW, very LBW, extremely LBW. (UNICEF, 2010). Quantitative and qualitative data were analyzed using Stata statistical version 14, logistic regression and NVivo version 14 respectively, Findings: â‰¥35 years of mothers OR=13.67, p=0.018, CL [1.55-120.12] and the second born children OR=2.98; p=0.025; CL [1.15-7.73] were associated with the overall LBW. Secondary level education OR=0.35; p=0.03; CL [0.14-0.91] was a protection against LBW. Meru OR=17.429, p=0.016, CI [1.7162-176.991] and other tribes OR=10.479, p=0.048, CI [1.025-107.124] were associated with low birth weight. Hypertension OR=3.59; p=0.038; CL [0.14-0.91] and malaria (OR=51.250, p=0.005, CL [3.185-822.132]) were associated with very LBW. ANC-attendance (OR=0.068, p=0.37, CL [0.0055-0.845]) was a protection against extremely LBW OR= 0.07; p=0,037; CL [0.01-0.85]. Unique Contribution to Theory, Policy and Practice: â‰¥35 years of mothers are risk factors for low birth weight. Second child is at risk of being low birth weight. Neonates of Meru origin and other minority ethnic groups in Thika are at risk of being LBW. Secondary level education is a protection against low birth weight. Hypertension and malaria are risk factors for very low birth weight. ANC-attendance is a protection against extremely low birth weight. The County Government of Kiambu should develop suitable strategies of strengthening maternal and child services at level one.